Kajian Strategis UMKM Kuliner Di Era Modern Di Kota Palangkaraya - Nanda Putri Qumayroh; Ira Veronika Girsang; Anita Anita; Rut Donda Damayanti L.B; Yulisia Nurike Manik; Benius Benius (JURNAL RISET MANAJEMEN DAN EKONOMI (JRIME), 2024)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in the Indonesian economy, contributing to job creation and economic growth. However, MSMEs often face various challenges, including intense competition, limited access to capital, and a lack of knowledge about marketing strategies and product diversification.This study aims to analyze the marketing strategies and product diversification implemented by four MSMEs in Indonesia: Paman Pentol (meatball seller), Lavaria Home (takoyaki and mozzarella corndog seller), goguma ppang (seller of bread made from sweet potato), and Es Doger (ice doger seller). This research uses a qualitative descriptive method with data collection techniques through interviews and observations, and documentation. The research findings indicate that the four MSMEs implement various marketing strategies and product diversification to increase sales and reach a wider market. Common marketing strategies include promotion through social media, discounts and attractive offers, and participation in local events. Product diversification undertaken by MSMEs includes developing new menus, offering combo packages, and selling products online. This study provides several important findings and recommendations for MSMEs. The key findings suggest that effective marketing strategies and product diversification can help MSMEs enhance their competitiveness and sustainability in the digital era. The main recommendations for MSMEs are to continuously innovate and adapt to market trends, improve product and service quality, and utilize digital technology to reach a wider customer base.